A new bioenergetic and thermodynamic approach to batch photoautotrophic growth of Arthrospira (Spirulina) platensis in different photobioreactors and under different light conditions. (May 2016) - da Silva, Milena Fernandes; Casazza, Alessandro Alberto; Ferrari, Pier Francesco; Perego, Patrizia; Bezerra, Raquel Pedrosa; Converti, Attilio; Porto, Ana Lucia Figueiredo
Highlights: Batch A. platensis culture is studied in different photobioreactor configurations. Kinetics, bioenergetics and thermodynamics of A. platensis growth are evaluated. An increase in surface/volume ratio up to 1.94 cm −1 enhanced growth parameters. The influence of light intensity is investigated in the horizontal photobioreactor. The horizontal photobioreactor has the best configuration to perform batch culture. Abstract: Photobioreactor configuration, mode of operation and light intensity are known to strongly impact on cyanobacteria growth. To shed light on these issues, kinetic, bioenergetic and thermodynamic parameters of batch Arthrospira platensis cultures were estimated along the time at photosynthetic photon flux density (PPFD) of 70 μmol m −2 s −1 in different photobioreactors with different surface/volume ratio ( S / V ), namely open pond (0.25 cm −1 ), shaken flask (0.48 cm −1 ), horizontal photobioreactor (HoP) (1.94 cm −1 ) and helicoidal photobioreactor (HeP) (3.88 cm −1 ). Maximum biomass concentration and productivity remarkably increased with S / V up to 1.94 cm −1 . HoP was shown to be the best-performing system throughout the whole runs, while HeP behaved better only at the start. Runs carried out in HoP increasing PPFD from 40 to 100 μmol m −2 s −1 revealed a progressive enhancement of bioenergetics and thermodynamics likely because of favorable light distribution. HoP appeared to be a promising configuration to perform high-yield indoor cyanobacterial cultures.